El panorama de México de Bullock-Burford, 1823-1864: historia de una pintura - Costeloe, Michael P. (El Colegio de México, A.C., 2010)
William Bullock (1773-1849) has a prominent place in museum history.  He assembled a vast natural history collection which, together with a myriad of other artifacts from around the world, he displayed in the Egyptian Hall, his specially constructed museum in London's Piccadilly. in 1823, accompanied  by his son, also William, he spent six months in Mexico. William Jun. made detailed sketches of Mexico City,  then the largest city in the American  hemisphere.  These drawings became the basis of a panoramic painting covering some 2700 square feet of canvas and designed to be displayed in a 360 degree rotunda. This work traces the history  of the painting, revealing for the first time its origins, ownership, travels, where and when it was exhibited in Europe  and the United  States, and its final destination at Burford's Panorama in Leicester Square.